PENDAMPINGAN PENYULUHAN BANTUAN HUKUM DALAM MEMBANTU MASYARAKAT/KELOMPOK KURANG MAMPU DI DESA JAMBON KECAMATAN JAMBON KABUPATEN PONOROGO - Lilik Prihatin; Anton Subagyo; Andik Wijaya (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
Legal Aid Counseling Assistance Activities in helping the underprivileged or underprivileged communities held in Jambon Village, Jambon District, Ponorogo Regency at the Jambon Village Hall. Based on the results of the implementation of legal counseling activities with the theme of Domestic Violence (KDRT) at the Jambon Village Hall, Jambon District, Ponorogo Regency, it can be concluded that the activity can be said to be carried out well and smoothly, which is marked by an active role, discussion and question and answer. with the community during the event. Furthermore, the assistance is not enough to end here, based on the evaluation results felt by the people of Jambon Village, especially at legal counseling activities, they are of the opinion that the legal counseling agenda can be carried out intensively and hope that there will be continuity of legal counseling and community empowerment.